The Emergent European Educational Policies Under Scrutiny. The Bologna Process from a Central European Perspective - Kwiek, Marek (My University, 2006)
The Bologna Process - creating a European Higher Education Area and the gradual, simultaneous emergence of a European Research Area - can be viewed as two sides of the same coin: that of the redefinition of the roles, missions, tasks, and obligations of the institution of the university in rapidly changing and increasingly market-driven and knowledge-based European societies and economies. Both teaching and research' are undergoing substantial transformation today, and the institution of the university, until fairly recently the almost exclusive host of the two interrelated activities, in all probability will be unable to avoid the process of substantial, partly planned and partly chaotic, transformation of its functioning. Whatever view we hold on the two parallel processes, they are already relatively well advanced in some countries and are promoted all over Europe, including in Central and East European accession countries and the Balkans. Whilst the effects of the emergence of the European Research Area are basically restricted to the beneficiaries of research funds available from the EU, the Bologna Process could potentially influence the course of reform in national higher education systems in 40 countries.
Keywords: Bologna Process; European integration; convergence; postcommunist countries; Central Europe; Eastern Europe; privatization; private sector; market; marketization; higher education research; Europeanisation; regionalisation; educational policy; postcommunism; higher education; public sector; European Research Area; ERA